A Modified Newton-type Method with Order of Convergence Seven for Solving Nonlinear Equations - Fang, Liang; Pang, Lin (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this paper, we mainly study the iterative method for nonlinear equations. We present and analyze a modified seventh-order convergent Newton-type method for solving nonlinear equations. The method is free from second derivatives. Some numerical results illustrate that the proposed method is more efficient and performs better than the classicalNewton's method.